2016
DOI: 10.1007/978-3-319-45719-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Extension-Based Ad Injection via Fine-Grained Web Content Provenance

Abstract: Extensions provide useful additional functionality for web browsers, but are also an increasingly popular vector for attacks. Due to the high degree of privilege extensions can hold, extensions have been abused to inject advertisements into web pages that divert revenue from content publishers and potentially expose users to malware. Users are often unaware of such practices, believing the modifications to the page originate from publishers. Additionally, automated identification of unwanted third-party modifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…The potential danger of extensions has been highlighted in [195] where extensions were identified to be "the most dangerous code to user privacy" in today's browsers. Some recent works have focused on tracking the provenance of web content at the level of DOM (Document Object Model) elements [23].…”
Section: Browser Extensionsmentioning
confidence: 99%
“…The potential danger of extensions has been highlighted in [195] where extensions were identified to be "the most dangerous code to user privacy" in today's browsers. Some recent works have focused on tracking the provenance of web content at the level of DOM (Document Object Model) elements [23].…”
Section: Browser Extensionsmentioning
confidence: 99%
“…Reis et al [26] proposed "web tripwires," a method that allows publishers to include a verification check in their page that compares the DOM a user received with the DOM the publisher sent. Arshad et al [4] developed OriginTracer, a tool that notifies the user about which party is responsible for any modifications in a loaded page's content by tracking DOM element alterations (e.g., due to browser extensions). The same authors have developed Excision [5], an in-browser mechanism that relies on an enhanced version of the DOM tree to keep track of the relationships between the resources of a page in order to block malicious third-party content.…”
Section: B Detecting Content Alteration and Fraudulent Ad Trafficmentioning
confidence: 99%
“…Extensions can be considered as the "most dangerous code in the browser" [9]. Previous research found extensions to inject or replace ads [1,10,29], causing monetary damage to content creators and, in turn, consumers. To detect privacy-invasive extensions, previous work used dynamic taint analysis to find spyware in Internet Explorer Browser Helper Objects (BHOs) [5].…”
Section: Introductionmentioning
confidence: 99%